Jesus and Mahomad are GOD. book 5 of the, 'God today' series - Foster, Bryan, 1957- (Gold Coast, Qld. : Great Developments Publishers, 2020)
Jesus and Mahomad are GOD' is the 5th book of 9 in the 'GOD Today' Series by author Bryan Foster. It is published by Great Developments Publishers, Australia. This book is based on the 15th of 21 Revelations sent by GOD to Bryan in 2016 and 2018 - GOD is Jesus and Mahomad. (#15) (Spelt this way by GOD.) These were received on two occasions around 3am, while Bryan Foster was caravan camping at the foot of Mt Warning in and near Murwillumbah, Australia. GOD directed Bryan to disseminate worldwide.
Keywords: God (Christianity); Private revelations; Spiritual life; God (Christianity); Philosophy & Religion; Private revelations; Spiritual life; Electronic books